Repositioning Strategy for Malaysian Companies Internationalization - Rajiani, Ismi; Buyong, Edna (UI Scholars Hub, 2013)
The rise of the emerging-market countries offers both developing and developed countries a unique opportunity to gain the benefits of a truly international economy. Consequently, it is imperative to advance our knowledge of emerging-market countries MNC emergence and competitiveness including Malaysian firms on how will they position their products strategically? Based on the framework of Porter’s Generic Strategy this paper is composed of price/ volume segments and impacts on product strategy theory. The aim is to identify crucial triggering cues and focus areas for Malaysian companies and measure what role these play in different segments. This study argues that some Malaysian companies will reposition themselves strategically when internationalizing and that they will focus on other factors or triggering cues when doing so not merely adapting the prevalent price leadership strategy.